Systemic resilience of the urban educational facility system: A spatiotemporal framework coupling chronic stresses and acute shocks - Ziteng Liu; Shichen Zhao; Ze Liu (Sustainable Cities and Society, 2026)

Diversified cropping combined with nutrient optimization regulates microbial resource limitations, thereby influencing ecoenzymatic carbon and nitrogen use efficiencies - Wei Zhang; Wanting Li; Zhuolin Li; Xinlei Li; Ruqi Duan; Dexiang Luo; Guohui Xiong; Mingmin Li; Jun Tao; Shichen Li; Yingfen Yang; Zhengxiong Zhao (Agriculture, Ecosystems & Environment, 2026)

Environmental and ecosystem economic benefits of optimized nitrogen management for tobacco production in subtropical region - Zhi Yao; Zheng Yuan; Guisu Zhou; Xingbang Wang; Liangjun Yu; Shichen Li; Zhengxiong Zhao (Environment, Development and Sustainability, 2026)

Exploring the spatial impact of China's government-led tourism development model on vernacular architecture in a traditional village - Peiyan Li; Kojiro Sho; P. Monica Chien; Shichen Zhao (Journal of Rural Studies, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Facet-dependent controls on antimony isotope fractionation during adsorption on hematite - Yan Zhang; Wenju Wang; Decan Tan; Jian-Ming Zhu; Peng Zhao; Ruxuan Jiang; Shichen Guo; Hai-Bo Qin (Applied Geochemistry, 2026)

Comparative neurotoxic effects of PFOA and GenX in hiPSC-derived cortical neurons - Han Zhao; Junkai Xie; Shichen Wu; Xihui Zhao; Serena Yu; Jennifer L. Freeman; Jean-Christophe Rochet; Chongli Yuan (Journal of Hazardous Materials, 2026)

Mechanistic insights into selective Pb(II) removal by magnetic sludge-derived biochar: A combined experimental and DFT study - Ermao Ding; Shichen Wang; Ke Zhao; Xiang Li; Zuoping Zhao (Journal of Environmental Management, 2026)

Plant litter addition promotes short-term improvement of saline-alkali soils through labile carbon and enzyme activities - Lirong Zhao; Yuyang Kou; Mengqi Zhang; Ni Gao; Ermao Ding; Shichen Wang; Kaiyang Han; Yixuan Liu; Minmin Qiang; Huan Ma; Liping Hu; Jun Meng; et al. (Journal of Soils and Sediments, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

Decreases in yield-scaled reactive nitrogen losses and nitrogen surplus by shifting rice-wheat rotation to ratoon rice mode in Southeast China - Jiarong Liu; Guangbin Zhang; Penghui Jin; Shichen Wang; Keda Jin; Jing Ma; Siyuan Cai; Xu Zhao; Shen Yuan; Shaobing Peng; Hua Xu; Xiaoyuan Yan (Field Crops Research, 2026)

A bHLH transcription factor negatively regulates effective panicle number and grain yield by modulating auxin transport and distribution in rice - Tao Yang; Rui Zhu; Jinlong Li; Yulong Wang; Lei Zhou; Qiaoqiao Zhao; Ningjia Jiang; An Zeng; Yanli Qin; Haixia Liu; Chenyu Xia; Shichen Han; et al. (Molecular Plant, 2026)

Optimizing soil health and maize yield in continuous cropping: synergistic effects of long-term straw return and winter land-use - Guiru ZHAO; Shichen LI; Chunhe JIANG; Xiaoyao DING; Feng ZHOU; Kaixian WU; Bozhi WU; Michael FULLEN (Pedosphere, 2026)

Critical role of mid-elevation in microbial regulation of soil carbon dynamics on the southern foothills of the Qinling Mountains - Ermao Ding; Fanglin Shen; Tengyue Du; Xian Ren; Shichen Wang; Lirong Zhao; Liping Hu; Jie Yang; Yue Hu; Weibo Shen (CATENA, 2025)

Resource utilization of microcrystalline magnesite: Synthesis of magnesium oxide by malic acid steam-assisted decomposition method for the synergetic adsorption of Congo red dye and Cu(II) ion - Jun Li; Ziyu Zhang; Rongzheng Gao; Xiaohui Li; Guoheng Sun; Ziye Zhou; Runtang Feng; Heqi Qi; Dong Zhang; Zihan Zhao; Shichen Xing; Dongmo Wu; et al. (Environmental Research, 2025)

Unraveling the role of pyrolysis temperature in biochar-mediated modulation of soil microbial communities and tobacco bacterial wilt disease - Shichen Li; Linyuan Yang; Tao Jiang; Waqar Ahmed; Fupeng Mei; Jinhao Zhang; Tao Zhang; Yingfen Yang; Xiaoci Peng; Qu Shan; Dexiang Luo; Zhengxiong Zhao (Applied Soil Ecology, 2025)

Distribution and air-sea fluxes of CO2 in coral reefs in the Greater Bay Area, China - Hongqiang Yan; Shichen Tao; Lijia Xu; Qi Shi; Yongzhi Wang; Meixia Zhao; Shengnan Zhou; Xiaoju Liu (Regional Studies in Marine Science, 2024)

Carbon budgets of coral reef ecosystems in the South China Sea - Hongqiang Yan; Qi Shi; Lijia Xu; Huiling Zhang; Meixia Zhao; Shichen Tao (Frontiers in Marine Science, 2024)
The coral reef ecosystem is one of the most productive ecosystems in the ocean, and is also an important calcium carbonate deposition region. Because excess production is very low in coral reefs, organic carbon reservoirs are very limited. During the calcification process, each mole of CaCO 3 will produce 1 mol of CO 2 , approximately 60% of which will be released into the atmosphere through the sea-air interface. This causes coral reefs to be large inorganic carbon reservoirs, but at the same time, most coral reefs act as atmospheric CO 2 sources (which also act as sinks in some coral reefs). Therefore, clarifying the sea-air CO 2 exchange flux and carbon storage is critical for understanding the carbon cycle in coral reef ecosystems. In this paper, we summarize the carbon cycle processes in the coral reefs of the South China Sea (SCS) and estimate the total CO 2 budget and carbon reserves. According to current research, the coral reefs in this area act as a source of atmospheric CO 2 , releasing 0.37−1.59 × 10 11 g C a -1 into the atmosphere. Owing to their extremely high biological productivity and carbonate productivity, the carbon reserves of coral reefs in the SCS range from 1.66–3.78 × 10 12 g C a -1 , which is an order of magnitude greater than the CO 2 emissions at the sea–air interface. Overall, coral reefs in the SCS are important carbon storage areas. As the current results are still approximate, a more comprehensive and in-depth investigation is needed to clarify the carbon source/sink processes, regulatory mechanisms, and carbon storage capacity of SCS coral reefs.

Environmental fate of microplastics in alpine and canyon-type river-cascade reservoir systems: Large-scale investigation of the Yalong River in the eastern Qinghai-Tibet Plateau - Yixuan Liu; Shaoting Zhao; Dongzhi Wang; Shichen Wang; Xiaofan Ding; Kaiyang Han; Ruiying Wang; Yuyang Kou; Guangqian Zhou; Weibo Shen (Science of The Total Environment, 2024)

Corrigendum to “Elevated parkinsonism pathological markers in dopaminergic neurons with developmental exposure to atrazine” [Sci. Total Environ. 908 2024: Article 168307] - Han Zhao; Junkai Xie; Shichen Wu; Xihui Zhao; Oscar F. Sánchez; Sehong Min; Sayan Dutta; Jean-Christophe Rochet; Jennifer L. Freeman; Chongli Yuan (Science of The Total Environment, 2024)

Sex-Dependent Lipid Profile Differences in Skin Mucus between Non-Parental and Parental Discus Fish (Symphysodon haraldi) Determined by Lipidomics - Shichen Zhao; Bin Wen; Hua Liang; Jianzhong Gao; Zaizhong Chen (Fishes, 2024)
Discus fish, Symphysodon spp., have a unique parental care strategy where the fry feed on their parents’ skin mucus after hatching. Here, lipidomics was employed to compare the skin mucus lipid profiles of male or female discus fish during parental and non-parental care. By multivariate statistical analysis, clear separations were found between parental and non-parental female and between parental and non-parental male discus. In the comparison between female discus in the parental and non-parental stages, a total of 107 differentially expressed lipids (DELs) were observed, of which 23 showed increased levels during parental care. For male discus, a total of 108 DELs were found, of which 46 displayed increased levels during parental care. The main DELs were phosphatidyl ethanolamine and phosphatidylinositol, mainly involved in arachidonic acid and sphingolipid metabolism pathways. Further, by comparing parental male and female discus, we found 47 DELs involved in the glycerophospholipid metabolism pathway. Diglyceride showed a higher concentration in the skin mucus of parental females, while phospholipids showed a higher level in that of parental males. Our results revealed changes in the skin mucus lipid profiles of discus fish during parental care, as well as sex-dependent differences between parental fish.

Elevated parkinsonism pathological markers in dopaminergic neurons with developmental exposure to atrazine - Han Zhao; Junkai Xie; Shichen Wu; Xihui Zhao; Oscar F. Sánchez; Sehong Min; Jean-Christophe Rochet; Jennifer L. Freeman; Chongli Yuan (Science of The Total Environment, 2024)

Different Morphologies and Functional Nitrogen Accumulation Results in the Different Nitrogen Use Efficiency of Tobacco Plants - Shichen Li; Waqar Ahmed; Tao Zhang; Tao Jiang; Fupeng Mei; Qu Shan; Linyuan Yang; Cuilian Guo; Zhengxiong Zhao (Journal of Plant Growth Regulation, 2023)

Pre-differentiation GenX exposure induced neurotoxicity in human dopaminergic-like neurons - Shichen Wu; Junkai Xie; Han Zhao; Oscar Sanchez; Xihui Zhao; Jennifer L. Freeman; Chongli Yuan (Chemosphere, 2023)

Coral growth over the past 550 years in the central South China Sea linked to monsoon- and seabird-induced nutrient stress - Yi Liu; Shichen Tao; Ruoyu Sun; Chen-Feng You; Tzu-Hao Wang; Thomas Felis; Wang Zheng; Shaobo Sun; Xiaodong Liu; Qi Shi; Jianxin Zhao; Kefu Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Acute Transcriptomic and Epigenetic Alterations at T12 After Rat T10 Spinal Cord Contusive Injury - Junkai Xie; Seth Herr; Donghan Ma; Shichen Wu; Han Zhao; Siyuan Sun; Zhixiong Ma; Matthew Yan-lok Chan; Katherine Li; Yang Yang; Fang Huang; Riyi Shi; et al. (Molecular Neurobiology, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Meridional response of Western North Pacific paleocyclone activity to tropical atmospheric circulation variability over the past millennium - Fei Tan; Yunfeng Zhang; Li Cao; Huilong Xu; Qi Shi; Xiyang Zhang; Shichen Tao; Jianxin Zhao; Hongqiang Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Identification of Potential Megalin/Cubilin Substrates Using Extensive Proteomics Quantification from Kidney Megalin-Knockdown Mice - Bei Zhao; Chengjian Tu; Shichen Shen; Jun Qu; Marilyn E. Morris (The AAPS Journal, 2022)

Identification of candidate genes for panicle length in Oryza sativa L. ssp. japonica via genome-wide association study and linkage mapping - Hongliang Zheng; Shichen Sun; Liangming Bai; Shukun Jiang; Guohua Ding; Tongtong Wang; Hongwei Zhao; Jingguo Wang; Hualong Liu; Luomiao Yang; Yan Jia; Xin Wei; et al. (Euphytica, 2022)

Immunoglobulin G Is a Novel Substrate for the Endocytic Protein Megalin - Mark A. Bryniarski; Bei Zhao; Lee D. Chaves; Jakob Hauge Mikkelsen; Benjamin M. Yee; Rabi Yacoub; Shichen Shen; Mette Madsen; Marilyn E. Morris (The AAPS Journal, 2021)

Effect of temperature, salinity, and body length on the energy budget of Daphniopsis tibetana Sars (Cladocera: Daphniidae) - Jie Wei; Wen Zhao; Shan Wang; Meiru Wang; Xiaoliang Wang; Shichen Ji; Hao An (Journal of Oceanology and Limnology, 2018)